(untitled) - United Nations Development Programme (UNDP) (NewYork, NY 10017, 2007)
In 2007, over a billion people had almost no income (the equivalent of a dollar a day or less for each). They typically spent more than half of what they did earn on food for their families, leaving even less for shelter, water, education and health care. Most of these people pooled their incomes through work that was insecure, underpaid and at times unsafe.
Keywords: Globalization,Toàn cầu hóa; Economic aspects,Khía cạnh kinh tế